Performance of SAC305 and SAC305-0.4La lead free electronic solders at high temperature. Issue 4 (2nd September 2019) - Aamir, Muhammad; Tolouei-Rad, Majid; Din, Israr Ud; Giasin, Khaled; Vafadar, Ana
Abstract : Purpose: Tin-Silver-Copper is widely accepted as the best alternative to replace Tin-Lead solders in microelectronics packaging due to their acceptable properties. However, to overcome some of the shortcomings related to its microstructure and in turn, its mechanical properties at high temperature, the addition of different elements into Tin-Silver-Copper is important for investigations. The purpose of this paper is to analyse the effect of lanthanum doping on the microstructure, microhardness and tensile properties of Tin-Silver-Copper as a function of thermal aging time for 60, 120 and 180 h at a high temperature of 150°C and at high strain rates of 25, 35 and 45/s. Design/methodology/approach: The microstructure of un-doped and Lanthanum-doped Tin-Silver-Copper after different thermal aging time is examined using scanning electron microscopy followed by digital image analyses using ImageJ. Brinell hardness is used to find out the microhardness properties. The tensile tests are performed using the universal testing machine. All the investigations are done after the above selected thermal aging time at high temperature. The tensile tests of the thermally aged specimens are further investigated at high strain rates of 25, 35 and 45/s. Findings: According to the microstructural examination, Tin-Silver-Copper with 0.4 Wt.% Lanthanum is found to be more sensitive at high temperature as the aging time increases which resulted in coarse microstructure due to the non-uniform distribution of intermetallic compounds. Similarly, lower values of microhardness, yield strength and ultimate tensile strength come in favours of 0.4 Wt.% Lanthanum added Tin-Silver-Copper. Furthermore, when the thermally aged tensile specimen is tested at high strains, two trends in tensile curves of both the solder alloys are noted. The trends showed that yield strength and ultimate tensile strength increase as the strain rate increase and decrease when there is an increase in thermal aging. Originality/value: The addition of higher supplement (0.4 Wt.%) of Lanthanum into Tin-Silver-Copper showed a lower hardness value, yield strength, ultimate tensile strength, ductility, toughness and fatigue in comparison to un-doped Tin-Silver-Copper at high temperature and at high strain rates. Finally, simplified material property models with minimum error are developed which will help when the actual test data are not available.